Dampak Penggunaan Pinjaman Online Terhadap Gaya Hidup Konsumtif Mahasiswa STIE Ekuitas - Mellya Putri; Reine Oktovina; Reina Oktovini; Indra Lesmana; Dito Rinaldo (Politeknik Negeri Ambon, 2023)
One of the digital financial services offered by financial service providers commonly called fintech is online loans. With easy terms and conditions, online loans make it easier for people, including students, to borrow money online. This service can influence students' consumptive lifestyle. Students who want to borrow money to meet their needs can take advantage of this online loan application, which allows money to be disbursed immediately. Loan repayment is considered easy because it can be paid in installments with a certain interest depending on the period chosen. The aim of this research is to find out how the use of online loan applications impacts the consumptive behavior or lifestyle of STIE Equity students. Students who used loan applications were surveyed via questionnaires. The research results show that the average student uses online loan applications because of necessity and is tempted by offers such as interest and price discounts.